Determination of HEPATOTROPIC effects of certain substances in experimental toxic hepatitis - Mustafakulov Muhammad Abduvalievich; Mallayeva Mavjudakhon Makhramovna; son of Qiyomov Ural Ali (Global Scientific Publishing, 2023)
Some substances have an antioxidant effect, it is necessary to study their pharmacological action and the mechanisms of their functioning. Various studies are being carried out to study the antioxidant effects of Beh and Summax. It was found in experiments that the activity of antioxidant enzymes in the composition of liver homogenate is corroded by the action of selected substances. An important place in the development of hepatitis in the liver is occupied by increased peroxidation processes, the formation of free radicals.
Keywords: toxic hepatitis; bex; quercetin; essential